2019
DOI: 10.1186/s12891-019-2977-2
|View full text |Cite
|
Sign up to set email alerts
|

Parallel comparison of fibroblast-like synoviocytes from the surgically removed hyperplastic synovial tissues of rheumatoid arthritis and osteoarthritis patients

Abstract: BackgroundFibroblast-like synoviocytes (FLS) are essential cellular components in inflammatory joint diseases such as osteoarthritis (OA) and rheumatoid arthritis (RA). Despite the growing use of FLS isolated from OA and RA patients, a detailed functional and parallel comparison of FLS from these two types of arthritis has not been performed.MethodsIn the present study, FLS were isolated from surgically removed synovial tissues from twenty-two patients with OA and RA to evaluate their basic cellular functions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…However, healthy individuals do not undergo therapeutic joint surgery, it is therefore difficult to obtain healthy FLS. As control FLS, we and others [ 39 , 40 , 41 ] therefore use FLS from patients with osteoarthritis (OA) which are less aggressive than RA-FLS in terms of migration, invasiveness, and production of cytokine, chemokines and growth factors [ 42 , 43 ]. Concentrations of 10 μg/mL PEG-HCCs and higher induce the death of both RA-FLS and OA-FLS ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, healthy individuals do not undergo therapeutic joint surgery, it is therefore difficult to obtain healthy FLS. As control FLS, we and others [ 39 , 40 , 41 ] therefore use FLS from patients with osteoarthritis (OA) which are less aggressive than RA-FLS in terms of migration, invasiveness, and production of cytokine, chemokines and growth factors [ 42 , 43 ]. Concentrations of 10 μg/mL PEG-HCCs and higher induce the death of both RA-FLS and OA-FLS ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Given that PEG-HCCs can enter FLS and reduce intracellular O 2 •− levels without affecting their survival at low doses, we next determined the effects of PEG-HCCs on FLS function. RA-FLS are more invasive and produce more pro-inflammatory cytokines and growth factors than do OA-FLS [ 42 ]. We therefore focused our analysis on the function of RA-FLS.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the proportion of CD34-THY1+ fibroblasts was correlated with the proportion of leukocyte infiltration, synovitis and synovial hypertrophy, which indicated that the altered proportion of fibroblast subsets in RA reflected the molecular level and clinical level of tissue inflammation. Huang et al (89) showed that some common fibroblast markers, consisting of procollagen I (COL1A1), Prolyl-4-hydroxylase (P-4-H), Vimentin, along with procollagen III (COL3A1), are different in OA FLS and RA FLS. Besides, RA FLS exhibits more severe cellular behavior in contrast with OA FLS, entailing a more rapid rate of proliferation, stronger invasive potential, and elevated expression as well as secretion of inflammatory cytokines.…”
Section: Dynamic Changes Of Synovial Fibroblast Subsets In Inflammatory Statementioning
confidence: 99%
“…Ревматоидный артрит (РА) -хроническое аутоиммунное заболевание, приводящее к поражению суставов и системным поражениям внутренних органов [17]. Известно, что РА характеризуется выраженным воспалительным статусом в отношении пролиферации, миграции, апоптоза, экспрессии генов и секреции провоспалительных цитокинов [23].…”
Section: Introductionunclassified
“…Это определяется типом клеток-мишеней, степенью их дифференцированности, а также особенностями функционирования внутриклеточных механизмов. Так, например, IL-4 и IL-10 ингибируют апоптоз Т-и В-лимфоцитов и индуцируют апоптоз циркулирующих моноцитов [23].…”
Section: Introductionunclassified